The distribution and redistribution of health resources in South Africa - Van den Heever, Alexander Marius (School of Economics, 2016)
This thesis is intended as a broad examination of the distribution of health resources in South Africa. Issues both macro and micro in nature have been covered to provide a perspective that would be Jacking in a narrower study. Although the title refers to a redistribution of resources, the intention of this thesis is to stress the importance of providing appropriate health measures rather than merely apportioning existing facilities evenly. This realization is insufficient, however, if it is not accompanied by the introduction and utilization of analytical approaches for identifying resource selection priorities. The influences on health status are many. In defining appropriate measures to improve health status it is important to be aware of the limitations of medical-care. Chapter three involves a cross-sectional regression analysis of various countries in order to examine the influences certain variables have on health status. This study suggests the need for an integrated approach to improving the health of a population. Merely focusing on medical care will only have a limited affect. However, this does not mean that medical-care is not important. It must just be provided in an appropriate manner. The rest of the thesis evaluates health-care resource distribution in South Africa. The existing distribution of health-care resources in South Africa is ill-suited to the existing health status of the population. There is a bias toward urban based curative facilities. Furthermore, the location of facilities has been based on racial criteria, whereby some areas have sufficient resources for their needs while others do not. Two methods of identifying how these issues should be dealt with are produced in this thesis. The first deals with a method for adjusting the broad distribution of funds toward those areas where need is greatest. The suggestion put forward by this thesis is that a formula be developed that would be able both to define need on a geographical basis, and to allocate resources based on that need. The formula would be used to allocate government health expenditure. This section is based on a formula that was developed in the United Kingdom. The second deals with a method for defining appropriate medical interventions on the micro level. It is called cost-effectiveness analysis (CEA). CEA is used for micro-economic decision-making where a choice has to be made between at least two alternatives for attaining a particular objective. Furthermore, CEA evaluates projects or programmes that are on-going in nature. It should be noted that CEA can also evaluate non-medical interventions to solve a particular health problem. In order to indicate the type of information that a CEA can provide, an investigation into cervical cancer procedures used on black females was produced. The entire black female population of South Africa was examined. A computer simulation of incidence and mortality rates of the disease was used to evaluate various scenarios. The results indicate that significant gains can be made by introducing cervical cancer screening on a large scale in South Africa. A major priority of this thesis was to stress the importance of using economic criteria to assist in making decisions concerning health-care resource allocations. Very little work of this nature is produced in South Africa. Hopefully this will not always be the case.